MicroRNA-29a plays a prominent role in PRIMA-1Met-induced apoptosis in ovarian cancer cells - İmir, Nilüfer Gülmen (Archives of Biological Sciences, 2020)
Paper description: This study investigates whether miRNA-29a has a potential role in PRIMA-1Met-induced apoptosis. Cell viability, apoptosis and miRNA-29a expression were examined by MTS, FACS analysis, and by RT-qPCR, respectively, in human ovarian cancer (Caov-3 (mutant p53)) and A2780 (wild-type p53) cells. The antitumor activity of PRIMA-1Met was independent of p53 in ovarian cancer cells, it induced apoptosis by increasing miRNA-29a. These results provide a basis for further studies aimed at elucidating the mechanism of Prima-1Met-induced apoptosis. Abstract: The structural analog of the small 2,2-bis(hydroxymethyl)-1-azabicyclo[2,2,2]octan-3-one molecule named PRIMA-1Metfor “p53 reactivation and induction of massive apoptosis” has been shown to inhibit cell growth and induce apoptosis in human tumor cells by restoring the tumor suppressor function of tumor protein p53. In several microRNA (miRNA) profiling studies related to ovarian cancer, different miRNAs associated with PRIMA-1Met have been reported, but miRNAs related to PRIMA-1Met-induced apoptosis remain unclear. This study was designed to explain the potential mechanism of PRIMA-1-induced apoptosis. According to the MTSassay and fluorescence-activated cell sorting (FACS) analysis results, PRIMA-1Met induced a significant decrease in cell viability and an increase in apoptosis in both A2780 and Caov-3 cells, regardless of p53 status. PRIMA-1Met upregulated miRNA-29a in both cell lines. To determine the effect of miRNA-29a on PRIMA-1Met-induced apoptosis, A2780 and Caov-3 cells were transfected with miRNA-29a inhibitor. After treatment with PRIMA-1Met, cell viability increased and apoptosis decreased in the transfected cells. The results of this study suggest that miRNA-29a potentially regulates PRIMA-1Met-induced apoptosis in ovarian cancer cells. https://doi.org/10.2298/ABS191128011I Received: November 28, 2019;Revised: February 12, 2020;Accepted: March 10, 2020; Published online: March 18, 2020 How to cite this article: İmir NG. MicroRNA-29a plays a prominent role in PRIMA-1Met-induced apoptosis in ovarian cancer cells. Arch Biol Sci. 2020;72(2):173-9.